DEVELOPMENT OF RATTAN PUPPET MEDIA AGAINST CLASS V JAVANESE LANGUAGE LEARNING OUTCOMES - Sari, Intan Purnama; Setyasto, Novi (Universitas Negeri Semarang, 2020)
This research was motivated by the results of Javanese language learning on some students who have not reached theMinimum Completion Criteria (MCC). One of the main factors causing these problems was the limitations of learningmedia. This type of research was development research. This study aimed to develop rattan puppet media, test thefeasibility of rattan puppet media, and test the effectiveness of rattan puppet media. The subjects of this study were gradestudents at elementary school Karasgede Rembang. The researcher used a saturated samples with 30 students. Datacollection used observation, interview, anghet, test, and documentation techniques. The researcher processed the data usingproduct data analysis, preliminary data analysis, and final data analysis, namely the t-test and gain test. The results showedthat rattan puppet media was very feasible to be used with the percentage of material experts evaluating by 95% and mediaexperts at 97%. Based on learning outcomes there were differences in average through the t-test of 7.047 and an averageincrease (gain) of 0.44796 with medium criteria. The conclusion of this study was that rattan puppet learning media wasvery feasible and effective to be used in Javanese language learning.